The Impact of Personal Income Distribution on the „Great Depression“ and the „Great Recession“ - Trappl, Stefan (Momentum Quarterly, 2015)
Well-known economists (Galbraith 1954/2009; Eccles 1951; Rajan 2010; Stiglitz 2012; Piketty 2014) identified “growing inequality” as one of the triggers of “Great Depression” respectively “Great Recession”. However there is little empirical evidence for this hypothesis. Kumhof/Ranciere (2010) built a theoretical model where they tested the “Rajan-hypothesis”, whereby growing income-inequality eventually caused the “Great Recession”. Bordo/Meissner (2012) and Gu/Huang (2014) used regression-models to show the relationship between growing inequality and the occurrence of crises. This paper examines the link between income inequality and the occurrence of crises – especially the “Great Depression” and the “Great Recession” – using a panel dataset containing information on eight countries for the period from 1920 to 2015. With a set of Generalized Linear Random-Effects-Regressions I tested whether income inequality can be identified as a significant predictor of crises. The models support the hypothesis of a positive relationship between growing inequality and the probability of the occurrence of crises.
Keywords: Personal Income Distribution; Great Depression; Great Recession; Random-Effects-Regression